Flutuação dos níveis de água subterrânea em microbacias hidrográficas do rio Vacacaí-Mirim - Farias, Pedro Vanerci da Cunha (2011)
The intention in this work is to study (locally) the fluctuation system of groundwater levels in two small watersheds. We selected Rancho do Amaral and Rincão do Soturno small watersheds for being representative of the first order streams which compose the Vacacaí-Mirim river watershed headwaters. Both are located at the border of Paraná Sedimentary Basin, in the central region of the state of Rio Grande do Sul. These small watersheds belong to the municipalities of Itaara and Santa Maria, and they are contributors of the Brazilian hydrographic region South Atlantic. They are considered exceptionally important for the municipality of Santa Maria because they are the main drinking water sources for the DNOS Dam at the Vacacaí-Mirim river. They belong to the system in which water is accumulated and provided to the population. The area under study is part of overlying sandstone in the Botucatu Formation, which belongs to the Guarani Aquifer System. In order to carry out the studies, three monitoring wells were made with equipment measuring the water levels and atmospheric pressure. The equipment was set to automatically take readings every hour. Based on the date collected from the equipment, we mounted a database and applied it to a specific computer program, which allowed us to adopt the Water Table Fluctuation (WTF) method. This method only applies to unconfined aquifers and measures direct groundwater recharges in drainage basins. The recharge was estimated to be 833.0 mm at well number 5; 746.2 mm at well number 6 and 467.2 mm at well number 7 during the period of evaluation. Therefore, the presence of groundwater recharge confirmed our work hypothesis.